Urgent-start Peritoneal dialysis, a challenge for the nephrologist - Palacios-Guillén, Alaciel (2023)
Peritoneal dialysis (PD) is a cost-effective therapy, little used worldwide. Urgent start PD is defined as the start of therapy in incident patients, immediately after or before two weeks after having placed a catheter for chronic PD in patients with chronic renal failure with indication of urgency dialysis, compared with the conventional start after two weeks. The objective was to review the current information on urgent start PD. A search was performed in PubMed, The Cochrane Library and SciELO. A total of 12 articles published up to October 31, 2021, were included. A low incidence of patients admitted to PD was found, even more so in urgent start PD. No significant differences were found that justify waiting to use the implanted catheter, thus avoiding hemodialysis in dialysis urgency. A meta-analysis with 16 studies (2953 patients) concluded that urgent start PD compared with conventional start did not increase death from any cause (1 RCT: RR 1.49, CI 95%: 0.87 to 2.53; 7 cohort studies: RR 1.89, CI 95%: 1.07 to 3.3, 1 case control study: RR 0.90, CI 95%: 0.27 to 3.02). Another meta-analysis with 6 studies (1242 patients) reports very low certainty in mortality (RR: 1.25, CI 95%: 0.92 to 1.69; I2=0%, p=0.99), mechanical complications with higher prevalence of leaks (RR: 6.72, CI 95%: 2.11 to 21.32; I2=0%, p=0.60), and there was no difference in infectious complications between the two groups. (RR: 1.36, CI 95%: 0.90 to 2.05, p=0.14). It is concluded that there is no significant difference between urgent start PD and conventional start, in patient survival or in the survival of the technique. The nephrology community should consider urgent start PD as a therapy option in patients requiring urgency dialysis.